Vulnerable Narcissism in Social Networking Sites: The Role of Upward and Downward Social Comparisons - Kong, Fanchang; Wang, Meiru; Zhang, Xingjie; Li, Xiaoyao; Sun, Xiaojun (Frontiers in Psychology, 2021)
Abstract: Social networking sites (SNSs) have provided a new platform for people to present narcissism. The current study aims to investigate the underlying mechanism between active and passive SNS uses and vulnerable narcissism among college students. Based on the media effect and social comparative theory, we recruited 529 participants to complete the Surveillance Use Scale, Iowa–Netherlands Comparison Orientation Measure, and Hypersensitivity Narcissistic Scale. Results showed that active and passive SNS uses are positively related to upward and downward social comparisons. Active and passive SNS uses indirectly predicted vulnerable narcissism through the parallel mediation of upward and downward social comparisons. This study reveals the vital role of social comparison in the association between SNS use and vulnerable narcissism.